The refugee swap deal in Malaysian Online News Reports: ideology and representation - Bolte, Stef; Yuen, Chee Keong (Penerbit UKM, 2014)
Using Critical Discourse Analysis, this study attempts to examine the representation of Refugees, Asylum Seekers and Immigrants (henceforth RASIM) in news reports from three selected English online newspapers in Malaysia: The Star, The New Straits Times (NST) and Malaysiakini. This research aims to reveal the representations of RASIM and attempts to unravel the ways in which ideology and context shape the discourse surrounding RASIM. The focus of the article is the Refugee Swap Deal between Australia and Malaysia that was announced in 2011. Although the Refugee Swap deal did not take place, the media discourse provided distinctive information about discursive strategies that media draw upon to represent RASIM. The general characteristics of the news reports disclose that there are ideological differences at play and that three main themes are frequently utilised to attribute certain characteristics to RASIM: refugee protection, people smuggling and human trafficking, and policy and national security. In Malaysian media, the reporting on RASIM has been framed according to the political stance of newspapers: in a positive supportive way by the government linked media, The NST and The Star, and in a more balanced way in the alternative, or non-government linked media, Malaysiakini. These reporting styles show differences in situational context and ideology that shaped the discourse of the newspapers, contributing significantly to the portrayal of RASIM in particular way